Regeneration of insertionally inactivated streptococcal DNA fragments after excision of transposon Tn916 in Escherichia coli: strategy for targeting and cloning of genes from gram-positive bacteria. - Gawron-Burke, C (1984)
The conjugative transposon Tn916 (15 kilobases), originally identified in Streptococcus faecalis DS16, has been cloned as an intact element on the pBR322-derived vector pGL101 in Escherichia coli. The EcoRI F' (EcoRI F::Tn916) fragment of pAM211 (pAD1::Tn916) was cloned into the single EcoRI site of pGL101 to form the chimera, pAM120, by selecting for the expression of Tn916-encoded tetracycline resistance (Tcr). Interestingly, in the absence of continued selection for Tcr, Tn916 excised from pAM120 at high frequency. This excision event resulted in a plasmid species consisting of the pGL101 vector and a 2.7-kilobase restriction fragment comigrating with the EcoRI F fragment of pAD1 during agarose gel electrophoresis. Filter blot hybridization experiments showed the 2.7-kilobase fragment generated as a result of Tn916 excision to be homologous with the EcoRI F fragment of pAD1. Analogous results were obtained with another chimera, pAM170, generated by ligating the EcoRI D' (EcoRI D::Tn916) fragment of pAM210 (pAD1::Tn916) to EcoRI-digested pGL101. Comparison of the AluI and RsaI cleavage patterns of the EcoRI F fragment isolated after Tn916 excision with those from an EcoRI F fragment derived from pAD1 failed to detect any difference in the two fragments: data in support of a precise Tn916 excision event in E. coli. Subcloning experiments showed that an intact transposon was required for Tn916 excision and located the Tcr determinant near the single HindIII site on Tn916. Although excision occurred with high frequency in E. coli, Tn916 insertion into the E. coli chromosome was a much rarer event. Tcr transformants were not obtained when pAM120 DNA was used to transform a polA1 strain, E. coli C2368.